Effect of Scarification Treatmens on Oleaster Seed Germination (Elaeagnus angustifolia L.) - Elahe Nikouee; Maryam Mollashahi; Alireza Moshki; Homan Ravanbaksh (علوم و فناوری بذر ایران)
Due to the fact that Elaeagnus angustifolia seed has a hard shell, the present study was conducted to investigate the types of appropriate treatments for germination of Elaeagnus angustifolia seed. The experiment was done in Semnan. Seed scarification performed in a completely randomized design with three replications (12 seed per replication). Experimental treatments to break dormancy of Elaeagnus angustifolia seed included control, 60% sodium hydroxide for 20 and 30 minutes, 98% sulfuric acid for 20 and 30 minutes, 1% oxygenated water for 10 and 20 minutes, physical scraping, 90°C boiling water for 15 minutes and ice water(5 days at a temperature of zero degrees and then 24 hours at a temperature of 25 degrees for 3 days). The results showed that there was a significant difference at the level of 1 % between the germination treatments of Elaeagnus angustifolia seed including of germination percent, germination rate, and mean time of germination seed vitality index, and seed vegetative traits such as root length, stem length, number of leaflets and seed germination indices. The highest germination percentage was 88.67% in 98% sulfuric acid treatment for 20 minutes. Also, the highest seed vigor index (96%), mean root length(48 mm), mean stem length(60 mm) and average number of leaflets (5.7 number) were observed in this treatment. Totally, the results showed that in all parameters examined that Sulfuric acid treatment of 98% for 20 years obtained the highest values, but two treatments of ice water and boiling water prevented the germination of Oleaster seeds.